TECHNOLOGY CODING TRANSFORMED VIDEO TOOLS IN UNEQUAL DIAGONAL-POSITIONAL SPACE - Shulgin, Sergii (Science-based technologies, 2022)
The article establishes that the security of the state and its sustainable economic development is associated with the level of quality of information support for critical infrastructure systems. It is shown that one the key factors here is the development of information communication technologies of the mobile segment, and the corresponding high-quality provision of services. It is substantiated that despite the constant increase in the productivity of information communications, there are problems with the quality of video information services. This situation is due to the presence an imbalance between the capacity of existing and promising telecommunication networks of the mobile segment and the level of information intensity of video traffic. The reason for this is the emergence of significant time delays arising in the process of proving video content, and a decrease in its quality under the QoS system. From where it is substantiated that the actual problem of research is to improve the quality of video information services from telecommunication networks of the mobile segment. To localize such an imbalance, it is proposed to use technologies to increase the information speed of video information transmission. To do this, use methods of compression of video information streams. The article proposes to use an approach based on the coding of video sequences in spectral space using the detection and elimination of structural patterns in the diagonal-spectral description of the transformer. Here, to build new approaches to encoding video tools, including informative video tools, it is proposed to use the theoretical foundations of unequal positional coding in spectral space. The article outlines the main stages of creating a technology for encoding transformed video sessions in an unequal positional space using the detection and elimination of the amount of redundancy, which is due to diagonal-spectral patterns. The method of automatic determination of the direction of indexing and values of the current positions of the components of diagonals by their initial coordinates in the two-dimensional structure of the transformer in conditions of arbitrary positioning of uneven diagonals relative to the half-zone of the transformer is constructed.